Fragmentos de um cotidiano abrigado: a institucionalização da sexualidade - Carvalho, Rita Ferreira de (2011)
This work discourse about the way as the sexuality and the body of the child is dealt inside the shelter houses, having as objective to discourse concerning the process of institutionalization of the infantile sexuality, investigating as the dynamics of the institution acts in the construction of the sexuality and, therefore, subjectivity of the child. For in such a way, based in the rules of the psychoanalysis, as investigative procedure had been carried through comments in an institution that shelters children moved away judicially from its family of origin. In this way, as resource for construction of material for analyzes searched to understand the unconscious aspects and the emotions take in the lived deeply relations that touch the limits of the institution, being been that the comments of the institutional dynamics had been carried through during a period of six months, with a weekly medium frequency, being these spaced per days and carried through in accordance with the possibility of the institution and the researcher. Of that what it was taken in consideration for our look and made direction, one searched to write down the impressions in a Daily of Field and, later, analyzes to carry through it of what it was observed to the light of the psychoanalysis method. Due to impossibility of if observing, to register and to analyze everything, were opted to analyze marking out with buoys it in the pieces that more token us front to the carried through comments. By means of it analyzes of the pieces was possible to construct hypotheses on the infantile shelters, the stigmatization of the intern and the institutionalization of the sexuality of the child. One concludes that a movement of burial of the psychic subject intern exists while, not being given to this the possibility to become subject in its proper history.